Space planning basics - Karlen, Mark; Fleming, Rob (Robert Michael) (2016)
"Space Planning Basics is the go-to guide for interior designers and space planners and in this extensive revision offers a complete learning solution for anyone in the early stages of their design"--
Includes bibliographical references and index.
Keywords: Interior architecture; Space (Architecture); ARCHITECTURE / Interior Design / General